Organization quality systems and department-level strategies: refinement of the Deepening our Understanding in Quality in Australia (DUQuA) organization and department-level scales. (5th February 2020) - Clay-Williams, Robyn; Taylor, Natalie; Winata, Teresa; Ting, Hsuen P; Arnolda, Gaston; Braithwaite, Jeffrey
Abstract: Objective: The aim of this study was to develop and refine indices to measure organization and care pathway-level quality management systems in Australian hospitals. Design: A questionnaire survey and audit tools were derived from instruments validated as part of the Deepening Our Understanding of Quality improvement in Europe (DUQuE) study, adapted for Australian hospitals through expert opinion. Statistical processes were used to explore the factor structure, reliability and non-redundancy and descriptive statistics of the scales. Setting: Thirty-two large Australian public hospitals. Participants: Audit of quality management processes at organization-level and care pathway processes at department level for three patient conditions (acute myocardial infarction (AMI), hip fracture and stroke) and senior quality manager, at each of the 32 participating hospitals. Main Outcome Measure(s): The degree of quality management evident at organization and care pathway levels. Results: Analysis yielded seven quality systems and strategies scales. The three hospital-level measures were: the Quality Management Systems Index (QMSI), the Quality Management Compliance Index (QMCI) and the Clinical Quality Implementation Index (CQII). The four department-level measures were: Specialised Expertise and Responsibility (SER), Evidence-Based Organisation of Pathways (EBOP), Patient Safety Strategies (PSS) and Clinical Review (CR). For QMCI, and for seven out of eight subscales in QMSI, adequate internal consistency (Cronbach's $α$ >0.8) was achieved. For CQII, lack of variation and ceiling effects in the data resulted in very low internal consistency scores, but items were retained for theoretical reasons. Internal consistency was high for CR (Cronbach's $α$ 0.74–0.88 across the three conditions), and this was supported by all item-total correlations exceeding the desired threshold. For EBOP, Cronbach's $α$ was acceptable for hip fracture (0.80) and stroke (0.76), but only moderate for AMI (0.52). PSS and SER scales were retained for theoretical reasons, although internal consistencies were only moderate (SER) to poor (PSS). Conclusions: The Deepening our Understanding of Quality in Australia (DUQuA) organization and department scales can be used by Australian hospital managers to assess and measure improvement in quality management at organization and department levels within their hospitals and are readily modifiable for other health systems depending on their needs.